2004
DOI: 10.1177/0310057x0403200615
|View full text |Cite
|
Sign up to set email alerts
|

Airway Obstruction following Carotid Endarterectomy

Abstract: Upper airway obstruction after carotid endarterectomy is a rare but potentially fatal complication of carotid endarterectomy. Upper airway obstruction is also a well recognized complication after neck surgery involving the thyroid gland and cervical spine. The airway obstruction usually develops slowly over a few hours and the onset is unpredictable. We report a patient who developed upper airway obstruction 16 hours following carotid endarterectomy. She required re-intubation in the intensive care unit (ICU).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Preoperative irradiation to the neck lesion would increase the risk of airway obstruction [14, 15], and the intraoperative prone position with the cervical spine in the flexed position could cause angioedema due to jugular venous congestion. Nömayr et al [16] investigated the MR imaging appearance of radiation-induced changes of normal cervical tissues among patients with primary neck tumor, and they found that oedema was the main radiation-induced effect.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative irradiation to the neck lesion would increase the risk of airway obstruction [14, 15], and the intraoperative prone position with the cervical spine in the flexed position could cause angioedema due to jugular venous congestion. Nömayr et al [16] investigated the MR imaging appearance of radiation-induced changes of normal cervical tissues among patients with primary neck tumor, and they found that oedema was the main radiation-induced effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical airway obstruction due to tissue edema or hematoma is a well-recognized surgical complication after various neck surgeries including thyroidectomy [ 138 ] and CEA [ 139 , 140 ]. Particularly during CEA, surgical procedures including dissection, traction, and retraction can injure the facial nerve, hypoglossal nerve, the vagus nerve including its branches (recurrent and superior laryngeal nerves), or glossopharyngeal nerve within the operative field [ 141 – 144 ].…”
Section: Safety Issues Related To Cervical Plexus Blocksmentioning
confidence: 99%
“…Nevertheless, some authors disagreed and stated that the trachea was rigid and diffi cult to compress. They reported that pharyngolaryngeal edema secondary to venous and lymphatic obstruction by hematoma was the mechanism of airway obstruction [5,[9][10][11]. In our case, the vocal cords could not be visualized and pha- ryngeal tissues were edematous at laryngoscopy.…”
Section: Discussionmentioning
confidence: 54%